DEMOCRACY, NEOLIBERALISM AND HUMANITARIAN CRISIS: anti-immigration policies and their effects on the democratic order. (Revista Paradigma, 2022)
This article aims to analyze the relationship between neoliberalism, democracy and human rights, in a context of humanitarian crisis in which there is an increase in the flow of migrants and refugees around the globe, showing a challenging scenario to countries that, although they consider themselves democratic, are not able to maintain the institutional commitments resulting from the choice of this political system. The research seeks to treat neoliberalism as the foundation of anti-immigration policies, in the light of the idea that this ideological current constitutes a mode of social regulation that seeks to annul individuality in favor of standardizing citizens to market interests, which allows the legitimization of these measures in the social scenario. In addition, it is the trend of political upward movement of outsiders in recent years, such as Donald Trump and Jair Bolsonaro, who, aware of the political dissatisfaction of elites with the government's compliance with minority agendas, including immigrants, seek to institutionalize political intensification and the ethnic rivalry between peoples, based on the denial of the other and differences, in an egocentric valorization of nationalism and the search for the reconstruction of national identity, leading to beliefs about the end or about a rupture in the current democratic model.